1996
DOI: 10.1116/1.580291
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of small molecules with TiO2(110) surfaces: The role of defects

Abstract: Articles you may be interested inInfrared spectroscopy study of adsorption and photodecomposition of formic acid on reduced and defective rutile TiO2 (110) surfaces J. Vac. Sci. Technol. A 32, 061402 (2014); 10.1116/1.4898568 Role of surface intermediates in enhanced, uniform growth rates of TiO2 atomic layer deposition thin films using titanium tetraisopropoxide and ozone J. Vac. Sci. Technol. A 30, 01A150 (2012); 10.1116/1.3669522 Structure, stability, and mobility of small Pd clusters on the stoichiometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 12 publications
2
26
0
Order By: Relevance
“…To further investigate the effects of temperature and pressure on the stability of various CO@Pt 14 /TiO 2 structures based on DFT calculations, the free energy diagrams were calculated based on DFT results and shown in Figure . It can be seen that for low values of CO chemical potential below −2.0 eV, the thermodynamically most stable structure is clean Pt 14 /TiO 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further investigate the effects of temperature and pressure on the stability of various CO@Pt 14 /TiO 2 structures based on DFT calculations, the free energy diagrams were calculated based on DFT results and shown in Figure . It can be seen that for low values of CO chemical potential below −2.0 eV, the thermodynamically most stable structure is clean Pt 14 /TiO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…A (5 × 2) TiO 2 (110) surface unit cell, a 1 x 2 k ‐point sampling set, and the theoretically derived lattice constants ( a = 4.69 Å, a = 2.99 Å, and u = 0.305) were used. Since the TiO 2 (110) slab is rather thin its redox state was controlled by adsorbed species on the slab surface rather than by bulk defects as proposed in prior work . Reduced slabs were realized by H adsorption on protruding Obr sites.…”
Section: Computational Detailsmentioning
confidence: 99%
“…In our experience, TiO 2 (110)-(1×2) surfaces contain a large number of oxygen vacancy lines due to the very large number of sputtering treatments. On the TiO 2 (110)-(1 × 1) surface, low densities of oxygen vacancies can lead to higher coverages and new redox reaction pathways for formic acid, but do not appear to alter the long range (2 × 1) ordering of saturated carboxylate layers [47][48][49][50]. In contrast, Bennett et al [51] have suggested that the oxygen vacancy lines or crosslinks are sites for preferential adsorption of formic acid on the (1 × 2) reconstructed surface.…”
Section: Tio 2 (110)-(1 × 2) Surfacementioning
confidence: 93%
“…Slightly sputtered rutile (1 1 0) surfaces have been used in many experiments in order to test the influence of surface reduction on adsorption of gases and metal overlayer growth [43][44][45][46][47][48]. Fig.…”
Section: Shown Inmentioning
confidence: 99%